The most important common and different points between the motives of old and new atheism - Al-Qahtani, Al-Bandari Ganim Saad (Journal of Humanities & Social Sciences, 2024)
This study sheds light on the most important common and different points about the motives of both old atheism and new atheism, and knowledge of the strategy and intellectual content of both. To achieve this goal, the study group used narrative, descriptive and analytical methods. A number of results have shown that the history of the emergence of ancient atheism appeared as a reaction to the oppression that occurred from the church in ancient times, while new atheism arose after the events of September 11, in which religions were rejected and slogans aimed at denying it were raised. There are also major differences between the intellectual content of the old atheism, which was based on philosophy and the desire to find several explanations about life, nature, and life, while the new atheism is largely in spite of the presence of some extended contents between them. Also, despite the presence of a simple and specific influence on the scene in ancient atheism, new atheism is still widespread to this day and with greater force at all religious, political, economic, social, and scientific levels, which has had a major impact on contemporary generations. Therefore, the researcher recommends the necessity of conducting broad research studies that include old atheism and new atheism in all its manifestations, so that it is an extensively comprehensive reference for the most important topics of both types, as well as paying attention to the presence of media outlets and research centers dedicated to confronting this ideological intellectual current that has invaded arenas of all kinds; Due to the great expansion that has become widespread among the young men and women of the Islamic nation today.